Educational Culinary Approach to Enhance Students' Interest, Skills, and Knowledge in Cooking at SMA Katolik Stella Maris Surabaya - Daniel Pandu Mau; Ivy Dian Puspitasari Prabowo; Elvin Adisatria Lukman (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Education in Indonesia often overlooked practical skills such as cooking, despite their importance for health and independence. This program implemented the Educational Culinary Approach at SMA Katolik Stella Maris in Surabaya to enhance students' interest, skills, and knowledge in cooking. The method involved preparation, planning, implementation, and evaluation of cooking training. Initial observations indicated that only 30% of students initially showed active interest in cooking activities. Following the training, results showed a significant increase in interest (90%) and cooking skills (80%) among students. Besides improving practical skills, the program integrated Catholic values such as social service. Group cooking activities provided psychosocial benefits, including enhanced self-confidence and social interaction. The final evaluation demonstrated that this program successfully enhanced students' holistic interests, skills, and knowledge in cooking. It proved that integrating academic education with practical skills could yield positive outcomes, both in practical skills and students' character and social development.